Evaluating Bioflocculation Harvesting of Freshwater and Marine Microalgae Using Exopolysaccharides (EPSs) from Klebsiella sp. - Yicheng Yuan; Jingxuan Lu; Quan Wang (Separations)
The rising global energy demand and environmental concerns associated with fossil fuels have intensified interest in sustainable biofuel sources, with microalgae emerging as a viable candidate due to its high biomass yield and efficient CO2 conversion. However, the economic feasibility of microalgal biofuels is currently challenged by costly harvesting processes. This study investigates the use of exopolysaccharides (EPSs) derived from Klebsiella sp. as an environmentally friendly bioflocculant for harvesting two microalgae species: Raphidocelis subcapitata and Dunaliella salina. Comparative flocculation experiments revealed that Klebsiella EPS promotes efficient aggregation in R. subcapitata, achieving over 90% flocculation efficiency, while performance with D. salina was impacted by high salinity, which reduced charge neutralization and bridging effects. Structural analyses using FTIR, 3D-EEM, CLSM, and XPS elucidated the EPS composition, underscoring the roles of polysaccharides and proteins in facilitating microalgal aggregation. The findings indicate that Klebsiella EPS offers a sustainable alternative to chemical flocculants, supporting eco-friendly biofuel production and potential applications in wastewater treatment. This approach provides insights into optimizing EPS-based flocculation for diverse environmental conditions, paving the way for more sustainable biomass recovery practices.